Influence of Quenchant Hydrodynamics and Boiling Phase Incipient Temperature Shifts on Residual Stress Formation - Vorster, W; Van Der Watt, M; Venter, A; Oliver, E; Prakash, D; Korsunsky, A (2009)
Quench heat treatments are used in metallurgical applications to alter material mechanical properties such as hardness and strength. Although these conventional heat treatments have been used for many decades, specific influences of material properties and heat transfer conditions during quenching are not very well understood. In particular, predictions based on steady-state boiling heat transfer coefficients disagree with observations, leading to the use of average uniform heat transfer coefficient applied over entire component surfaces as a rule of thumb, with adjustments made for particular processes and components. This paper investigates the effects of multiphase boiling heat transfer and transitional nucleate boiling regimes on the final residual stress states within components. The results of this study show that correct representation of heat transfer conditions provides significant improvements over the current quench modeling techniques, ultimately allowing production of engineering components with superior mechanical properties, reduced distortion, and well-controlled beneficial residual stress states.